Happiness at Work: Case of Apparel Industry in Sri Lanka - Silva, O.; Siriwardhane, D.; Hettiarachchi, A. (My University, 2022)
The objectives of the study were to; examine the differences in happiness at work among white-collar and blue-collar workers in the apparel industry and to explore the main contributing organizational level factors to happiness at work. Following the case study method, a sample of blue and white-collar employees, selected from a large organization in the apparel industry were used to collect data. A structured questionnaire was used to collect data related to happiness and its determinants. Both ANOVA and ANCOVA models together with qualitative analysis were used to analyze data. It was found that blue-collar workers are happier at work than white-collar workers. Furthermore, it was discovered that job inspiration and work-life quality are the most significant contributors to the happiness of blue-collar employees; job inspiration, leadership, and work quality contribute to the happiness of white-collar employees.
Keywords: Blue-collar employees, Happiness at work, Job inspiration, Job satisfaction, Well-being of employees, White-collar workers